2013
DOI: 10.1001/jamadermatol.2013.398
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sunscreens on Preventing UVR-Induced Effects in Nevi

Abstract: IMPORTANCE Sun damage is the most important environmental factor associated with malignant melanoma. To address the health threat, as well as the economic burden, primary prevention and early detection are crucial.OBJECTIVE To test the efficacy of a topical sunscreen in the prevention of UV-induced effects in nevi.DESIGN Prospective study of nevi protected by sunscreen vs a physical barrier.SETTING AND PATIENTS Twenty-three nevi from 20 patients attending a referral hospital.INTERVENTION Half of each nevus was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Primary prevention and early detection are crucial to addressing the health threat and economic burden of SMM [ 40 ]. We recommend that the general population should take measures to minimize their exposure to risk factors, such as avoiding exposure to intermittent high-dose sunlight as well as other types of ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary prevention and early detection are crucial to addressing the health threat and economic burden of SMM [ 40 ]. We recommend that the general population should take measures to minimize their exposure to risk factors, such as avoiding exposure to intermittent high-dose sunlight as well as other types of ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that the general population should take measures to minimize their exposure to risk factors, such as avoiding exposure to intermittent high-dose sunlight as well as other types of ultraviolet radiation. Studies have indicated that although correctly using sunscreen can reduce the SMM incidence [ 40 ], traditional protection methods (e.g., wearing protective clothing and avoiding sun exposure or prolonged sunbathing) are more effective in reducing the melanoma risk [ 40 , 41 ], and these measures cannot be replaced by sunscreen use [ 42 ]. To optimize protection from the damaging effects of the sun, we should, therefore, not just “slop on the sunscreen” but also “slip on a t-shirt, slap on a hat, seek shade, and slide on sunglasses.” Importantly, these measures should be implemented together, not just one or some of them [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated melanocytic activation and cell proliferation in nevi after a single dose of UV-B. 48,49 Inflammation-induced changes and melanocytic activation can in fact be observed in vivo, with RCM revealing the presence of intraepidermal dendritic cells and bright particles at DEJ and papillary dermis. If RCM features were evaluated in isolation and without knowledge that the nevus was recently irradiated by UVR, the RCM features would lead to the false diagnosis of melanoma (presented by Takigami MC et al at the 73rd American Academy, San Francisco, unpublished data, 2015).…”
Section: Challenging Lesions On Reflectance Confocal Microscopy: Pitfmentioning
confidence: 99%
“…After two UVB minimal erythema doses marked melanocytic activation was reported, avoided by physical and sunscreen protection [22]. Another study found that even after a single dose of UVB clinical and dermoscopic changes in nevi occurred, partially prevented by physical barriers or sunscreens [23]. Moreover, a positive correlation of the extent of morphological changes with increasing total…”
Section: Assessment Of Cnn Scoresmentioning
confidence: 99%